Answer:
x1 = -7+3t
x2 = (11-7t)/2
Explanation:
Given the system of equations
x1 − 3x3 = −7 ...,...... 1
3x1 + x2 − 2x3 = −5 ....... 2
2x1 + 2x2 + x3 = −3 ....... 3
Setting x3 = t.
Substitute x3 = t into equation 1 to get x1 in terms of t.
x1 − 3x3 = −7
x1-3(t) = -7
x1-3t = -7
Add 3t to both sides;
x1-3t+3t = -7+3t
x1 = -7+3t
To get x2, substitute x1 = -7+3t and x3 = t into equation 3
2x1 + 2x2 + x3 = −3
2(-7+3t)+2x2+t = -3
Open the parenthesis
-14+6t+2x2+t = -3
Collect like terms
2x2+6t+t = -3+14
2x2+7t = 11
Subtract 7t from both sides
2x2+7t-7t = 11-7t
2x2= 11-7t
Divide both sides by 2
2x2/2 = (11-7t)/2
x2 = (11-7t)/2
Hence the solution to the system if equation (x1, x2, x3) = (-7+3t, (11-7t)/2, t)